Human antibody responses to dengue virus infection: involvement of antibodies against mosquito salivary proteins and alpha-gal glycan - Olajiga, Olayinka Moyosoluwa (Kansas State University, 2022)
The family Flaviviridae member dengue virus (DENV), which is transmitted by Aedes mosquitoes, is the etiology of dengue fever. Dengue is one of the fastest-growing reemerging mosquito-borne diseases in the world and poses a threat to roughly half of the world's population with a 30-fold increase in the last five decades. During feeding, salivary proteins and viral pathogens are introduced into the host skin through mosquito salivation. These salivary proteins influence systemic and local (skin) immune responses. There is evidence that Ae. aegypti salivary gland extract, the Nterm peptide from Ae. aegypti 34-kDa salivary protein, and two new salivary proteins- Ae. aegypti bacteria-responsive protein 1 (AgBR1) and neutrophil stimulating factor 1 (NeSt1) have modulatory properties on flavivirus infection. In addition, an immunogenic glycan, galactose-alpha1,3-galactose (alpha-Gal or aGal), shown to be in DENV-2 envelope protein may function in dengue infection process. Therefore, in order to understand how human antibodies respond to Ae. aegypti salivary proteins as well as antibodies response to the aGal found on the DENV envelope associated with dengue infection, we used an ELISA technique to detect antibodies levels against salivary proteins in two-hundred and one serum samples and aGal in seventy-five serum samples from volunteers living in a dengue fever endemic region of Colombia in 2019 and 2020, respectively. We found that antibody levels against each salivary protein and aGal varied in the time course of dengue infection depending on the severity. An evolutionary analysis of DENV serotype 1, which circulates in the endemic region of Colombia with the highest frequency, showed clustering of the sequence with the typical South American DENV serotype 1 viruses. Our findings highlight the need for thorough studies on the roles and mechanisms of action of salivary proteins and aGal antibodies in dengue infection, as well as for ongoing epidemiological monitoring of dengue in the population.
Keywords: Dengue; Febrile; Antibodies; Salivary proteins; Alpha-gal